Mutation in the putative ketoacyl-ACP reductase CaKR1 induces loss of pungency in Capsicum - Koeda, Sota; Sato, Kosuke; Saito, Hiroki; Nagano, Atsushi J.; Yasugi, Masaki; Kudoh, Hiroshi; Tanaka, Yoshiyuki (Theoretical and applied genetics, 2019)
Key message A putative ketoacyl-ACP reductase ( CaKR1 ) that was not previously known to be associated with pungency of Capsicum was identified from map-based cloning and functional characterization. The pungency of chili pepper fruits is due to the presence of capsaicinoids, which are synthesized through the convergence of the phenylpropanoid and branched-chain fatty acid pathways. The extensive, global use of pungent and non-pungent peppers underlines the importance of understanding the genetic mechanism underlying capsaicinoid biosynthesis for breeding pepper cultivars. Although Capsicum is one of the earliest domesticated plant genera, the only reported genetic causes of its loss of pungency are mutations in acyltransferase ( Pun1 ) and putative aminotransferase ( pAMT ). In this study, a single recessive gene responsible for the non-pungency of pepper No.3341 ( C. chinense ) was identified on chromosome 10 using an F 2 population derived from a cross between Habanero and No.3341. Five candidate genes were identified in the target region, within a distance of 220 kb. A candidate gene, a putative ketoacyl-ACP reductase ( CaKR1 ), of No.3341 had an insertion of a 4.5-kb transposable element (TE) sequence in the first intron, resulting in the production of a truncated transcript missing the region coding the catalytic domain. Virus-induced gene silencing of CaKR1 in pungent peppers resulted in the decreased accumulation of capsaicinoids, a phenotype consistent with No.3341. Moreover, GC–MS analysis of 8-methyl-6-nonenoic acid, which is predicted to be synthesized during the elongation cycle of branched-chain fatty acid biosynthesis, revealed that its deficiency in No.3341. Genetic, genomic, transcriptional, silencing, and biochemical precursor analyses performed in combination provide a solid ground for the conclusion that CaKR1 is involved in capsaicinoid biosynthesis and that its disruption results in a loss of pungency.